Optimization of process parameters for the production of an OTA-hydrolyzing enzyme from Aspergillus niger under solid-state fermentation - Abrunhosa, Luís (2011)
Ochratoxin A (OTA) is a mycotoxin found in several food and feed products. Due to its acute toxicity, innovative biological strategies to degrade OTA have been sought. In previous studies, Aspergillus niger MUM 03.58 was found to produce one promising OTA-hydrolyzing enzyme for food and feed applications. In this paper, we describe the optimization of a solid-state fermentation (SSF) process to produce this enzyme using the one-factor-at-a-time and the Taguchi experimental design approaches. A preliminary evaluation of the fermentation time, substrate moisture content and type of carbon source was done by the one-factor-at-a-time method. A final maximization of the OTA-hydrolyzing enzyme production was done using Taguchi’s experimental design. An L9 orthogonal array was used to evaluate the effect of four factors at three levels. The substrate composition, the fermentation time, the operating temperature and the moisture content of the substrate were the factors evaluated. The results were tested by ANOVA and optimum conditions for a verification test were determined by statistical calculations. The optimized conditions were 30 g of wheat bran at 70% moisture incubated for 14 days at 25°C. A final productivity of 154 U/g substrate was achieved, which represents an approximately 3.7-fold increase in enzyme yield when compared with the starting point conditions.